PENGARUH PNPM MANDIRI TERHADAP TINGKAT PERTUMBUHAN EKONOMI MASYARAKAT (STUDI KASUS KECAMATAN SUMOBITO KABUPATEN JOMBANG) - arif, syamsul; Kumalasari, Retno Dwi (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2017)
ABSTRACTPNPM Mandiri (National Community Empowerment Program) has now begun to show its effectiveness at the level of economic growth of the people of Sumobito Sub-district, Jombang Regency which will increase the economic income of the community. With such a thing PNPM Mandiri will make the program to be maintained until the community Sub Sumobito Jombang Regency really uplifted his standard of living. The results of the research conducted by linear regression found that there is a positive effect of PNPM Mandiri revolving loan on the level of economic growth of the community. This can be shown from the t value obtained by PNPM Mandiri (X) = 18,638 with a sig rate of 0,000 indicates that there is a positive influence between PNPM Mandiri on community economic growth, and a significant result of 0,000 indicates that the value is less than 0 , 05 means to have a significant influence between PNPM Mandiri (X) on the economic growth of society (Y). Thus Ho is rejected and H1 accepted as a hypothesis which states there is a significant influence of PNPM Mandiri partially on the economic growth of society (Y) in Sumobito District Jombang.Â Keywords: PNPM Mandiri (National Program for Community Empowerment),economic growth